Surface modification by alkali and heat treatments in titanium alloys - Lee, BH; Kim, YD; Shin, JH; Lee, KH (WILEY, 2002)
Pure titanium and titanium alloys are normally used for orthopedic and dental prostheses. Nevertheless, their chemical, biological, and mechanical properties still can be improved by the development of new preparation technologies. This has been the limiting factor for these metals to show low affinity to living bone. The purpose of this study is to improve the bone-bonding ability between titanium alloys and living bone through a chemically activated process and a thermally activated one. Two kinds of titanium alloys, a newly designed Ti-In-Nb-Ta alloy and a commercially available Ti-6Al-4V ELI alloy, were used in this Study. I this study, surface modification of the titanium alloys by alkali and heat treatments (AHT), alkali treated in 5.0M NaOH solution, and heat treated in vacuum furnace at 600 C, is reported. After AHT, the effects of the AHT on the bone integration property were evaluated in vitro. Surface morphologies of AHT were observed by optical microscopy (OM) and scanning electron microscopy (SEM). Chemical compositional surface changes were investigated by X-ray diffractometry (XRD), energy dispersive spectroscopy (EDS), and auger electron spectroscopy (AES). Titanium alloys with surface modification by AHT showed improved bioactive behavior, and the Ti-In-Nb-Ta alloy had better bioactivity than the Ti-6Al-4V ELI alloy in vitro. (C) 2002 Wiley Periodicals, Inc.
Keywords: IN-VITRO; TI-6AL-4V; TI; DIFFERENTIATION; HYDROXYAPATITE; RELEASE; ABILITY; INVIVO; CO; CR